Perencanaan Strategis Penggunaan Teknologi Informasi Dalam Bisnis Keuangan ( Studi Kasus Bank Muamalat) - Fahmi, Khairul; Batubara, Soraya Alyya Syam; Simamora, Nur Ainun; Lubis, Dian Zahra Syahfitri; Rahma, Maulida; ., Nurbaiti (Journal Of Informatics And Busisnes, 2023)
Along with the rapid development of technology, almost all sectors of life utilize information technology to carry out business processes to keep them running. The corporate world also does not want to be left behind in developing information technology. This is done to improve business quality and customer satisfaction. This research aims to find out about strategic planning for the use of information technology in the strategic financial business of sharia banking in Indonesia. This type of research is in the form of literature study. . The development of sharia banking based on information technology will be very helpful in controlling increased public access to various online financial service products. Bank Muamalat's efforts to accelerate digital technology are first by developing a mobile banking application that can be used by customers to carry out financial transactions and view account information from anywhere, an example of using mobile banking is the M-DIN application.